The Influence of Using Clustering Technique Towards Students’ Exposition Paragraph Writing Ability at The Second Semester of the Tenth Grade of MAN 1 Tanggamus in 2015/2016 Academic Year - Meisuri, Meisuri; Wahyuni, Sri (English Education: Jurnal Tadris Bahasa Inggris, 2016)
This research is conducted based on the phenomena taking place in school that are many students often consider writing difficult. The students are not interested in the technique of English teacher; students also are lack of motivation in learning writing. The students’ exposition paragraph writing score is below the criteria of minimum mastery (KKM) at MAN 1 Tanggamus. Therefore, this research discusses the influence of using Clustering Technique in teaching writing, especially for students’ exposition paragraph writing ability. The objective of the research is to find out whether there is influence of Clustering Technique towards students’ exposition paragraph writing ability at the second semester of the tenth grade of MAN 1 Tanggamus, Lampung in 2015/2016 academic year. The methodology of this research was quasi experimental design with the treatment held in 3 meetings, 2 x 45 minutes for each. The population of this research was tenth grade students of MAN 1 Tanggamus, Lampung. The total sample in this research was 53 students that were taken from two classes, X.I and X.2. In collecting the data, the researcher used instruments, pre-test and post-test. The instrument was exposition paragraph writing test. After giving the post-test, the researcher analyzed the data by using independent sample t-test. From the data analysis, it was found that the result of calculating was tobserved (5.94) with tcritical (1.6759), it means that the score of tobservedwas higher than tcritical, so Ho was refused. So, there was influence of Clustering Technique towards students’ exposition paragraph writing ability at the second semester of the tenth grade of MAN 1 Tanggamus, Tanggamus, Lampung.